Ultrasound assessment of hepatomegaly and metabolically-associated fatty liver disease among a sample of children: a pilot project - Riestra-Candelaria, Bárbara L.; Rodríguez-Mojica, Wilma; Vélez-Morell, Camille; Ramírez-Marcano, Claudia; Alvarado-Castillo, Ariana; Camareno-Soto, Gabriel; González-Rodríguez, Loida A. (Frontiers in Pediatrics, 2025)
IntroductionObesity in children is a global health crisis, with 46% of children in Puerto Rico classified as overweight or obese based on Body Mass Index. This condition is linked to serious comorbidities, including early-onset type 2 diabetes, hypertension, and Metabolic-Associated Fatty Liver Disease (MAFLD), the most common liver disease in U.S. children. This study examines the relationship between body weight, liver size, and texture in children from Puerto Rico.MethodsA craniocaudal right liver lobe (RLL) measurement was performed using a panoramic ultrasound image. RLL length and liver texture were assessed based on fat infiltration. BMI was calculated to classify participants into healthy and unhealthy weight groups, and waist circumference (WC) was compared. Statistical analyses, including Shapiro–Wilk, Student's t-tests, ANOVA, and post hoc Tukey HSD, were conducted with significance at p ≤ 0.05.ResultsForty-three children aged 7–19 years were recruited. Significant differences were observed in liver size and texture between healthy and unhealthy weight groups: RLL length (p = 0.003), WC (p < 0.001), and BMI (p < 0.001). Obese children had significantly larger RLL and WC than healthy-weight group (p = 0.02; p < 0.001). More children in unhealthy weight group exhibited hepatomegaly (n = 12) and fat infiltration (n = 15).DiscussionThe findings indicate that large liver and MAFLD are common among children with overweight and obesity, suggesting liver changes related to obesity begin early in life. Strategies to maintain a healthy weight in children are essential to reduce the risk of chronic diseases and potential disabilities in adulthood.